Quantifying long-term impacts of COVID-19 and oil price shocks in a Gulf oil economy - Manal Shehabi (The Oxford Institute for Energy Studies, 2021)
The COVID-19 pandemic had been particularly deleterious on economies that export commodities with volatile prices. The effects have been visible even in the relatively wealthy yet hydrocarbon-overdependent Gulf Cooperation Council (GCC) states. Notwithstanding differences among them, GCC states faced adverse effects of the pandemic along with expanded economic stimulus packages and a simultaneous large drop in oil export revenue and government budgets. These dynamics are problematic to the extent that they affect current economic development and become enduring and foundational if the energy transitions accelerate to meet the Paris Agreement targets. In the context, this paper investigates the following questions: (a) what are the long-term impacts of oil price declines and COVID-19 associated shocks on Gulf economies?; and (b) what lessons can be drawn from the pandemic and domestic policy responses to it for the future management of the accelerating energy transitions and enhancing economic sustainability? This paper applies the economy-wide WAFRA Applied General Equilibrium (WAFRAGE) Model for Kuwait (WAFRAGE-KWT), which represents oligopoly behaviour and embodies key economic features and distortions. It is calibrated to a database in the form of a Social Accounting Matrix (SAM), constructed for this study and the first to represent Kuwait's economy in a low oil price environment. Simulations confirm that Kuwait's economic resilience has significantly weakened post-COVID. The cost of pandemic is proportionate to the length of pandemic and dependent on government's economic responses to it and oil market dynamics. Yet across all scenarios, fiscal cushions and savings are eroded and all macroeconomic indicators decline. Real wages of unskilled Kuwaiti labour decline, while foreign labour wages and employment are largely hit. Household welfare and firms counterintuitively improve owing to government's relief packages, but without a corresponding expansion in production, efficiency, output, or non-oil exports. This paper makes important contributions to the literature of hydrocarbon exporters. It is the first known study to quantify economy-wide impacts on a Gulf state of the pandemic along with policy responses to it and oil price declines. Model simulations show that, although COVID relief packages appear counter-cyclical, the full potential benefits of such a fiscal policy cannot be realized owing to these states' economic structure and consumption-based nature of their relief packages. In the absence of a diversified export base, the combination of a weakened economic resiliency and eroded fiscal cushions/savings post-pandemic jeopardize the economy's ability to survive the next large shocks in oil prices and demand following accelerated energy transitions or other crises. The results confirm a large trade-off between short terms economic recovery gains and long-term sustainability goals. Restoring long-term sustainability requires immediate yet phased implementation of urgent wide-scale fiscal, economic, microeconomic, and energy reforms.
Keywords: 330; Oil price; covid-19; coronavirus; Post-COVID economy; economy-wide modelling; CGE model; general equilibrium; oil exporter; resource exporter; Gulf; Kuwait; MENA